2021
DOI: 10.1093/wbro/lkab008
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Beliefs: Why They Matter and What They Are

Abstract: Teacher effectiveness is low in many developing countries. How can it be improved? We show that understanding teacher beliefs may be an important but overlooked part of the puzzle. Our review of recent evidence shows that teacher beliefs can impact student outcomes directly; they can also mediate policy implementation. Despite this, we find that teacher beliefs are seldom accounted for or even measured in impact evaluations of teacher-focused programs. Most of these programs ultimately fail to change teacher b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 51 publications
0
19
0
1
Order By: Relevance
“…Indeed, children from low-SES backgrounds are the target of negative intellectual stereotypes. Around the world, individuals from low-SES backgrounds are seen as less competent 12 and less able to develop their competence through effort and learning 13 compared to their high-SES peers. Children readily pick up on these harmful ideas and potentially internalize them as self-perceptions.…”
Section: Self-perceptions As Mechanisms Of Achievement Inequalitymentioning
confidence: 99%
“…Indeed, children from low-SES backgrounds are the target of negative intellectual stereotypes. Around the world, individuals from low-SES backgrounds are seen as less competent 12 and less able to develop their competence through effort and learning 13 compared to their high-SES peers. Children readily pick up on these harmful ideas and potentially internalize them as self-perceptions.…”
Section: Self-perceptions As Mechanisms Of Achievement Inequalitymentioning
confidence: 99%
“…Empirical evidence indicates that a substantial proportion of teachers in low-income contexts hold limiting beliefs about disadvantaged students' intelligence and potential. A World Bank survey of 16,000 teachers from eight low-and middle-income Latin American, African, and Asian countries found that more than 60 percent of teachers agree that students deserve more attention if they have the necessary resources and materials, which suggests an attention bias towards more socio-economically advantaged students (Sabarwal et al, 2021). Between 24 and 62 percent of teachers believed that they would not be able to help students learn if their families had too many personal or financial struggles; and in seven of the eight countries surveyed, between 24-50 percent of teachers believed that if a student's parents lacked education, there would be little they could do in the way of helping students learn.…”
Section: What Is the Empirical Evidence On Teacher Beliefs About Disa...mentioning
confidence: 99%
“…Teacher beliefs about and corresponding behavior towards disadvantaged learners remain a relatively under-explored factor, however, especially in low-income contexts. This is somewhat surprising because evidence from Western contexts suggests that teacher beliefs and expectations can be an important driver of educational outcomes, especially for disadvantaged students (Diamond et al, 2004;Sabarwal et al, 2021). Teacher beliefs and attitudes are not only important because of their putative effect on learning outcomes, but also because of their intrinsic value: all children deserve to be treated with kindness and dignity and to be encouraged to perform to the best of their abilities, regardless of their social or ethnic background.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In purpose-driven teacher career structures, 'fairness' in compensation is based on shared goals (rather than administrative defaults) To illustrate this contextual diversity of beliefs about fairness in compensation, a survey of 20,079 teachers in nine developing countries found wide variation in the proportion of teachers who agreed that they should receive financial bonuses if their students did well in official exams-ranging from less than 20 percent of teachers in Argentina and Indonesia to more than 90 percent of teachers in Pakistan and Tanzania (Sabarwal et al, 2021). Such differences in perceptions likely have realworld implications for teachers' motivation and wellbeing, as well as the quality of their work.…”
Section: → See Alsomentioning
confidence: 99%